2020
DOI: 10.1038/s12276-020-00505-7
|View full text |Cite
|
Sign up to set email alerts
|

The role of natural killer cells in Parkinson’s disease

Abstract: Numerous lines of evidence indicate an association between sustained inflammation and Parkinson’s disease, but whether increased inflammation is a cause or consequence of Parkinson’s disease remains highly contested. Extensive efforts have been made to characterize microglial function in Parkinson’s disease, but the role of peripheral immune cells is less understood. Natural killer cells are innate effector lymphocytes that primarily target and kill malignant cells. Recent scientific discoveries have unveiled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 134 publications
(206 reference statements)
0
37
0
Order By: Relevance
“…Thus, changes in the expression levels of CD11b and CCR2 in iRBD supports a role for these proteins in the neurodegenerative process in synucleinopathies. Interestingly, CCL2 can also recruit NK cells (29), which are found in PD brain (30) and increased in PD blood (31). The iRBD patients had increased mature NK cells, which constitute those of higher CD16 expression and that possess cytotoxic capacity (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, changes in the expression levels of CD11b and CCR2 in iRBD supports a role for these proteins in the neurodegenerative process in synucleinopathies. Interestingly, CCL2 can also recruit NK cells (29), which are found in PD brain (30) and increased in PD blood (31). The iRBD patients had increased mature NK cells, which constitute those of higher CD16 expression and that possess cytotoxic capacity (29).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, CCL2 can also recruit NK cells (29), which are found in PD brain (30) and increased in PD blood (31). The iRBD patients had increased mature NK cells, which constitute those of higher CD16 expression and that possess cytotoxic capacity (29). Interestingly, it is suggested that NK cells might have a protective role by clearing a-syn (30).…”
Section: Discussionmentioning
confidence: 99%
“…This upregulation suggests NK cell activation and that the cells are more prone to kill senescent cells, e.g. those burdened with α-syn (24).…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the increased expression of CD16 on NK cells might contribute to the neurodegeneration mediated by the adaptive immune response. However, NK cells can also clear α-syn (44), thus they seem relevant for balancing the neuroprotective and neurodegenerative immune processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation